The effects of epigenetic regulation on phenotypic expressivity in Turkish patients with familial Mediterranean fever - Eser Dogan; Semra Gursoy; Giray Bozkaya; Secil Arslansoyu Camlar; Ozge Aksel Kilicarslan; Alper Soylu; Ayfer Ulgenalp; Salih Kavukcu; Ozlem Giray Bozkaya (Indian Journal of Rheumatology)
Introduction: In this study, we aimed to characterize the effect of methylation on clinical diversity and gene expression levels in familial Mediterranean fever. Materials and Methods: Forty children, who were diagnosed with FMF according to the Tel-Hashomer criteria, were included in the study. The control group consisted of 32 healthy children. Demographic data, results of molecular studies, physical examination findings, number of attacks, response to treatment were recorded. To test the possibility that methylation is responsible for different phenotypic reflections of mutations, we classified FMF patients with respect to MEFV mutations and studied the differences of MEFV mRNA, pyrin and methylation levels between different subgroups. Results: MEFV mRNA expression levels were significantly lower in FMF patients, compared to control subjects (P = 0.049). Consistent with this observation, pyrin levels were significantly lower in FMF patients (P = 0.037). In addition, we found that MEFV methylation level was higher in FMF patients compared to control subjects (P = 0.376). Conclusions: There was no evidence that differences in methylation levels could be responsible for variable effects of different mutations and variable clinics in the MEFV gene. Further studies on larger patient groups are necessary to identify the effects of different factors.